Pengembangan Media Layanan Informasi Berbasis Web untuk Pemahaman Karir Siswa - Musfira, Yuni; Muslima, Muslima (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
This study aims to develop a web-based career information service media to assist students of SMPN 7 Banda Aceh in understanding career paths that align with their interests and talents. The research method used is Research and Development, following the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The study subjects consisted of 30 ninth-grade students selected for field testing. The research results showed that junior high school students face limited access to career information and highly require media that facilitates easier access to such information. The developed web-based career information service media includes features such as job descriptions, educational pathways, and an interactive discussion forum. Based on the field test, 88% of students reported an improvement in their understanding of career options after using the media. Student satisfaction with the media was also very high, with 90% of respondents giving positive feedback on its accessibility and ease of use. Assessments from media experts and career counseling experts indicated that the media has a responsive and user-friendly design, while the information provided was considered comprehensive and relevant. Thus, this web-based career information service media has proven effective in helping students understand various career options and educational pathways, making it suitable for wider implementation in schools